2020
DOI: 10.3390/tropicalmed5030148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Three-Year Intermittent Preventive Treatment Using Artemisinin-Based Combination Therapies on Malaria Morbidity in Malian Schoolchildren

Abstract: Previous studies have shown that a single season of intermittent preventive treatment in schoolchildren (IPTsc) targeting the transmission season has reduced the rates of clinical malaria, all-cause clinic visits, asymptomatic parasitemia, and anemia. Efficacy over the course of multiple years of IPTsc has been scantly investigated. Methods: An open, randomized-controlled trial among schoolchildren aged 6–13 years was conducted from September 2007 to January 2010 in Kolle, Mali. Students were included in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…SMC in children aged 3-59 months remains a promising strategy for malaria control in countries with seasonal malaria transmission. SMC leads to considerable reductions in morbidity and mortality associated with malaria [7,8,[17][18][19][20]. Studies in Africa have shown that SMC has a remarkable impact in reducing cases of uncomplicated malaria, hospitalizations and deaths related to malaria [15,18,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…SMC in children aged 3-59 months remains a promising strategy for malaria control in countries with seasonal malaria transmission. SMC leads to considerable reductions in morbidity and mortality associated with malaria [7,8,[17][18][19][20]. Studies in Africa have shown that SMC has a remarkable impact in reducing cases of uncomplicated malaria, hospitalizations and deaths related to malaria [15,18,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…It is also recommend that at least school-aged children in the study area to be treated for asymptomatic P. falciparum . 41 These findings indicate the need for a comprehensive intervention plan that should combine ongoing treatment campaigns against schistosomiasis and STHs with other interventions to reduce the intensity of parasites, prevent the possibility of re-infection, and thereby reduce the morbidities. 15 These highly prevalent infections and significant morbidities alert the concerned bodies to give urgent special attention to the area, to achieve the global control and elimination targets of these infections.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-eight studies were conducted in hospitals (68%) and nine in health centres (22%) [35,36,39,40,42,51,56,62,63]. Eight studies were conducted in health clinics (20%) [29,30,39,43,49,57,61,64]. Two studies were conducted in basic health facilities (5%) [59,65].…”
Section: Location and Settingmentioning
confidence: 99%
“…One study included a dispensary [56]. Seven studies included rural health facilities [3,30,43,48,49,62,63].…”
Section: Location and Settingmentioning
confidence: 99%